Salafiyah Curriculum at Islamic Boarding School in the Globalization Era - Indra, Hasbi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract This paper discusses the curriculum of traditional Islamic boarding school in the current globalization era. This institution was born in the era of Walisongo during the colonial period established by the society. In this period, traditional Islamic boarding schools are confronted with the complicated problems. Nowadays, Pesantren becomes a part of a national education system, and it is projected to have a high-level Quality education. In the current condition, pesantren is confronted with the challenges of globalization with negative and positive effects. The development of science and technology gives an ease for humans life nowadays. The economic nowadays is more developed and brings a free trade among Asian. In this era, Pesantren as an institutional education is a part that could pay attention for it. Pesantren in the future should give knowledge to santri dealt with broader perspectives in Islamic knowledge, as well as in science and technology, economic and also give attention to santri about entrepreneurship to enhance their skill of life and then could compete with others in this world. This research is qualitatively based on the sources of some books and journals from scholars that describe the development and challenges of Islamic boarding school and how the institutions are confronted with phenomenon of current globalization era. Abstrak Tulisan ini membahas kurikulum pesantren tradisional di era globalisasi saat ini. Lembaga ini lahir di era Walisongo selama periode kolonial yang didirikan oleh masyarakat. Pada kurun waktu tersebut, pesantren dihadapkan dengan masalah yang rumit. Saat ini, pesantren menjadi bagian dari sistem pendidikan nasional, dan pesantren diproyeksikan untuk memiliki kualitas pendidikan yang tinggi. pada kondisi saat ini, pesantren dihadapkan dengan berbagai tantangan globalisasi dengan dampak negatif dan positif. Pesantren di masa depan sebaiknya memberikan pengetahuan kepada para santri untuk berurusan dengan perspektif yang lebih luas dalam pengetahuan Islam, serta sains dan teknologi, ekonomi, dan juga memberikan perhatian kepada para santri tentang kewirausahaan untuk meningkatkan keterampilan hidup sehingga dapat bersaing dengan orang lain di dunia ini. Penelitian ini secara kualitatif berdasarkan pada sumber-sumber beberapa buku dan jurnal yang menggambarkan perkembangan dan tantangan pesantren dan bagaimana lembaga dihadapkan dengan fenomena era globalisasi saat ini. How to Cite : Indra, H. (2017). Salafiyah Curriculum at Islamic Boarding School in the Globalization Era. TARBIYA: Journal of Education in Muslim Society, 4(1), 74-88. doi:10.15408/tjems.v4i1. 4960. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.4960